Highly Efficient Synthesis of Polysubstituted 2-Aminopyrroles via a Multicomponent Domino Reaction - Shao, Jiaan; Ke, Di; Shu, Ke; Chen, En; Yu, Yongping; Chen, Wenteng (Synlett, 2018)
A highly efficient approach to polysubstituted 2-aminopyrroles containing a coumarin derivative unit at the 5-position of the pyrrole ring was developed via a novel multicomponent domino reaction of glyoxal monohydrate derivatives, anilines, coumarin derivatives, and malononitrile. This transformation proceeded via an α-aminoketone as the key intermediate.
Keywords: 2-aminopyrroles; domino reaction; multicomponent reaction; coumarin derivatives; heterocycles